The effect of competition style on developing some physical attributes and basic skills of soccer players (Journal of the College of Basic Education, 2022)
The research included presenting its introduction and its importance, then the research problem formulated by the researcher that there is a need to pay attention to the use of modern training methods to develop physical attributes and skillful performance as well as the research goal of recognizing the impact of competition style in developing some physical attributes and basic skills of football players, and the researcher used the competitive method in The training units of the research sample, after conducting the tests and analyzing their results, it was found that there is a statistically significant difference between the pre and post tests in favor of the post test.